2021
DOI: 10.3390/cancers13061373
|View full text |Cite
|
Sign up to set email alerts
|

Serum Exosomes and Their miRNA Load—A Potential Biomarker of Lung Cancer

Abstract: Early detection of lung cancer in screening programs is a rational way to reduce mortality associated with this malignancy. Low-dose computed tomography, a diagnostic tool used in lung cancer screening, generates a relatively large number of false-positive results, and its complementation with molecular biomarkers would greatly improve the effectiveness of such programs. Several biomarkers of lung cancer based on different components of blood, including miRNA signatures, were proposed. However, only a few of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 39 publications
(33 citation statements)
references
References 169 publications
0
33
0
Order By: Relevance
“…Extracellular vesicles circulating in the biofluids of cancer patients, which represent a mixture of TEX and other classes of vesicles released by “normal” types of cells, are a potential source of diagnostic and prognostic biomarkers. Numerous studies tested protein and RNA components of such vesicles in the context of lung cancer [ 21 ]. Several lung cancer signatures were proposed based on proteins present in serum/plasma-derived sEV [ 22 , 23 , 24 , 31 , 32 ], and more reports focused on the miRNA cargo of serum/plasma-derived sEV.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Extracellular vesicles circulating in the biofluids of cancer patients, which represent a mixture of TEX and other classes of vesicles released by “normal” types of cells, are a potential source of diagnostic and prognostic biomarkers. Numerous studies tested protein and RNA components of such vesicles in the context of lung cancer [ 21 ]. Several lung cancer signatures were proposed based on proteins present in serum/plasma-derived sEV [ 22 , 23 , 24 , 31 , 32 ], and more reports focused on the miRNA cargo of serum/plasma-derived sEV.…”
Section: Discussionmentioning
confidence: 99%
“…Several lung cancer signatures were proposed based on proteins present in serum/plasma-derived sEV [ 22 , 23 , 24 , 31 , 32 ], and more reports focused on the miRNA cargo of serum/plasma-derived sEV. According to the current literature review, miRNA signatures of lung cancer have been reported in about 30 papers [ 21 ]. These signatures contained about 60 miRNA species overall, including 14 miRNA species that appeared in multiple signatures (exemplified by the oncomir miR-21).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we found that the top 11 signi cantly changed miRNAs (hsa-miR-221-3p, hsa-miR-222-3p, hsa-miR-133a-3p, hsa-miR-222-5p, hsa-miR-204-3p, hsa-miR-145-5p, hsa-miR-3681-5p, hsa-miR-184, hsa-miR-144-3p, hsa-miR-204-5p, and hsa-miR-221-5p) were deregulated in prostate cancer with bone metastasis malignant transformation. It has been reported that miR-221 may be a potential prognostic biomarker of hepatocellular carcinoma, lung cancer, and breast cancer and a critical regulator of therapeutic susceptibility in breast cancer [21][22][23]. The active cells in bone include osteoblasts, osteoclasts, hematopoietic cells, adipocytes and various immune cells.…”
Section: Discussionmentioning
confidence: 99%